Developing County Associations for School and Community Gardens - John M. Diaz; Susan Tyler Webb; Erin Elsberry (EDIS)
Increasingly, gardeners receive attention for the educational, environmental, health, and social impacts that their projects facilitate within schools and communities. Garden associations allow Extension to play a vital role in providing technical information to support new and existing gardens. This 3-page fact sheet outlines the framework used by a pilot garden association program in Polk County, Florida. Written by John M. Diaz, Susan Tyler Webb, and Erin Elsberry, and published by the Department of Agriculture Education and Communication, March 2017.